Nitrogen removal performance and microbial diversity of bioreactor packed with cellulosic carriers in recirculating aquaculture system. (February 2021) - Chen, Zhao; Chang, Zhiqiang; Qiao, Ling; Wang, Jiajia; Yang, Ligan; Liu, Yunfeng; Song, Xiefa; Li, Jian
Abstract: In this research, a solid-phase denitrification reactor (SPDR) packed with corrugated paperboard was introduced into the recirculating aquaculture system (RAS) of Litopenaeus vannamei for nitrate removal. Results showed that 82.88% of the nitrogen was removed from the culture water with the denitrification rate of 0.74 mg L −1 ·d −1 and the concentration of nitrate was controlled at 2.31 ± 1.00 mg L −1 . High throughput sequencing analysis showed that the corrugated paperboard was degraded by Lachnospiraceae, Saprospiraceae, Exiguobacterium, Mesoflavibacter, etc. to provide carbon source for denitrifying bacteria, including Rhizobiaceae, Rhodobacteraceae, Bacillus, Nitratireductor, Sphingobium, Marinicella, Desulfovibrio, Marinobacter, and Labrenzia . The abundance of the functional genes amoA, nirK, and nosZ indicated that nitrogen can be efficiently converted into N2 in the SPDR. Highlights: Corrugated paperboard was used for denitrification in the recirculating aquaculture system. Denitrification efficiency was measured by mass balance and stable isotope dilution method. Denitrifying bacteria was revealed via high-throughput sequencing based on gene 16S rRNA, nirS, and nirK. Nitrogen cycle path was revealed by the abundance gene amoA, nirS, nirK, and nosZ.